Poly-extremophiles: exploring the limits of habitability - Maizel, Daniela (2019)
Brevibacterium linens AE038-8 is an arsenic hyper-tolerant bacterial strain, previously isolated from well water in Tucumán, Argentina. The aim of this study is to investigate the resistance of this strain to different stress factors relevant for astrobiology studies. We found that B. linens AE038-8 is capable of tolerating high concentrations of heavy metals such as Cd(II), Cr(VI) and Cu(II), and a range of temperatures from 10 to 30°C. It is also able to grow in the range of pH values from 3 to 11, and when grown in the presence of NaCl, it can tolerate concentrations up to 5 M. We also study the ability of the strain to grow under combined stress conditions. In particular, we found that it is able to grow under high NaCl concentrations and low pH, conditions relevant to the habitability of brines in Mars.